Toward Technology-Based Education and English as a Foreign Language Motivation: A Review of Literature - Wei, Yi (Frontiers in Psychology, 2022)
This review examined the studies on the role of technology-based English as a foreign language (EFL) academic motivation. A significant positive correlation between academic motivation and educational technology use has been approved in related studies. However, there is a dire need for studying the effect of Mobile-Assisted Language Learning (MALL) and Computer-Assisted Language Learning (CALL) on learners’ motivation. The literature showed that purposeful attractiveness, effectiveness, and usefulness of digital instruments can positively affect learner motivation. There are also some reasons for increasing learner motivation in educational technology contexts, such as learners’ integration with the community, familiarising with different societies and cultures, input flooding opportunities, engagement in academic contexts, and interaction with native speakers. In the end, the paedagogical implications are expounded to promote the learners’ grit and diminish anxiety for better performance. This review also provides suggestions for further research to clarify our perspective on emotional variables like motivation.